Trends and inequalities in anaemia prevalence among children aged 6-59 months in Ghana, 2003-2022 - Augustus Osborne; Khadijat Adeleye; Camilla Bangura; Florence Gyembuzie Wongnaah (BMC, 2024)
Abstract Background Anaemia, characterised by a deficiency in red blood cells or haemoglobin, is a public health issue in Ghana, particularly among children. The prevalence of anaemia in this age group has been a longstanding concern due to its adverse effects on cognitive development, physical growth, and well-being. This study examined the trends and inequalities in anaemia prevalence among children aged 6-59 months in Ghana between 2003 and 2022. Methods Data from the Ghana Demographic Health Survey conducted between 2003 and 2022 was used to analyse the prevalence of anaemia in children aged 6-59 months. The World Health Organization's Health Equity Assessment Toolkit software calculated several inequality measures, including difference, ratio, population-attributable risk, and population-attributable percentage. An inequality assessment was performed for six stratifiers: child's age, mother's economic status, maternal educational level, place of residence, child's sex, and sub-national region. Results Anaemia prevalence among children aged 6-59 months in Ghana declined from 76.1% in 2003 to 48.9% by 2022. The results revealed an age-related inequality in anaemia prevalence among children in Ghana, with younger age group ( 6-11 months) consistently showing higher rates. The age-related inequality Difference was 24.6 percentage points in 2022, indicating that age is crucial to understanding anaemia risk. Economic-related inequality between children of mothers in Quintile 5 (richest) and Quintile 1 (poorest) increased from a Difference of 21.1 percentage points in 2003 to 32.7 percentage points in 2022 highlighting the stark inequalities across wealth quintiles. Education inequality between children of mothers with higher education and no education decreased from a Difference of 29.4 percentage points in 2003 to 25.3 percentage points in 2022, suggesting that children from less educated households are still at higher risk. Place of residence inequality between children of mothers living in urban areas and rural areas increased from a Difference of 12.3 percentage points in 2003 to 14.8 percentage points in 2022 reflecting urban-rural disparities. Sex-related inequality between male and female children decreased from a Difference of -0.3 percentage points in 2003 to -5.5 percentage points in 2022 indicating the absence of inequality based on sex of the child. Lastly, regional inequalities are pronounced, as indicated by an increase in the Difference from 21.2 percentage points in 2003 to 34.0 percentage points in 2022, highlighting that children in certain regions like the Northern and Upper East are more affected by anaemia. Conclusion The decline in anaemia prevalence among children aged 6-59 months in Ghana, reflects substantial progress; however, notable inequalities persist across age, economic status, education, place of residence, and region. To address these disparities, strategies such as enhancing access to healthcare services in underserved regions, implementing community education programs to raise awareness about nutrition and health, and promoting economic empowerment initiatives can be effective. Additionally, community education can play a crucial role in offsetting the effects of low household education levels, fostering a more informed population that can advocate for better health practices and policies. By addressing these key areas, we can work towards reducing anaemia prevalence and improving child health outcomes across all populations in Ghana.